Systematic training model for teaching, development and training of instructors in inguinal hernia treatment using the Lichtenstein technique. Hernia campaign 2014 & 2015. - LAZZARINI-MENDES,CARLOS JOSÉ (2016)
ABSTRACT Objective: to evaluate the method of training and continuing education of 18 surgeons in 2014, and 28 surgeons in 2015, in the Holy Homes of Ribeirao Preto, Araraquara, Franca and San Carlos of São Paulo, in the performance of Lichtenstein inguinal herniorrhaphy, tutored by the Faculty of Medical Sciences of the São Paulo Holy Home and the organization HERNIA HELP - "Hernia Repair for the Underserved". Methods: the training was tutored and systematized through an active methodology of teaching and learning, aiming to offer competence, skills and attitudes, measured by a previously validated Qualification Form, qualifying leaders in trainees' improvement. Results: in 2014 the outcomes were: the difficulty of the case, direction, incision, dissection, mesh preparation, mesh cutting, mesh setting, closing, instruments, respect to tissues, flow, time and motion, and performance, all presented change in the general rating (p=0.000002); there was greater confidence in the execution of the procedure in 80% of trainees, considered "very valuable" in 93.3% of the interventions. In 2015, 28 surgeons were trained by ten surgeons previously qualified in 2014. The nerve identification rate, a relevant time the Lichtenstein technique, was 95.5% for the Iliohypogastric, 98.5% for the ilioinguinal and 89.4% for the genital branch of the genitofemoral nerve. Conclusion: the applied teaching method is possible, reproducible, reliable and valid. The joint efforts offer enormous opportunity of directed education, reaching underserved populations, revealing the great teacher-student social responsibility.